Ornately decorated pillar base - Temples of India Project Team (Jio Institute, 2024)
A small shrine, possibly a newer construction, is placed off-centred to the right facing the garbhagriha. Further steps lead to the third level, on a projected platform. Pieces from the temple have been repurposed in this shrine. The structure has arched openings on the west, east, and north sides with a rectangular entrance inside an arched niche (seen here) on the south side.